The synergic effect of water and biomolecules in intracellular phase separation - Ribeiro, Sara S. (2019)
Phase separation has long been observed within aqueous mixtures of two or more different compounds, such as proteins, salts, polysaccharides and synthetic polymers. A growing body of experimental evidence indicates that phase separation also takes place inside living cells, where intrinsically disordered proteins and other molecules such as RNA are thought to assemble into membraneless organelles. These structures represent a new paradigm of intracellular organization and compartmentalization, in which biochemical processes can be coordinated in space and time. Two thermodynamic driving forces have been proposed for phase separation: the strengths of macromolecule-macromolecule and macromolecule-H2O interactions, and the perturbation of H2O structure about different macromolecules. In this Perspective, we propose that both driving forces act in a concerted manner to promote phase separation, which we describe in the context of the well-known structural dynamics of intrinsically disordered proteins in the cellular milieu. We further suggest that this effect can be extended to explain how the partial unfolding of globular proteins can lead to intracellular phase separation.